Intravenous Tissue Plasminogen Activator in Stroke Mimics: Findings From the Get With The Guidelines–Stroke Registry. Issue 8 (August 2019) - Ali-Ahmed, Fatima; Federspiel, Jerome J.; Liang, Li; Xu, Haolin; Sevilis, Theresa; Hernandez, Adrian F.; Kosinski, Andrzej S.; Prvu Bettger, Janet; Smith, Eric E.; Bhatt, Deepak L.; Schwamm, Lee H.; Fonarow, Gregg C.; et al.
Abstract : Background: The necessity for rapid evaluation and treatment of acute ischemic stroke with intravenous tPA (tissue-type plasminogen activator) may increase the risk of administrating tPA to patients presenting with noncerebrovascular conditions that closely resemble stroke (stroke mimics). However, there are limited data on thrombolysis safety in stroke mimics. Methods and Results: Using data from the Get With The Guidelines–Stroke Registry, we identified 72 582 patients with suspected ischemic stroke treated with tPA from 485 US hospitals between January 2010 and December 2017. We documented the use of tPA in stroke mimics, defined as patients who present with stroke-like symptoms, but after workup are determined not to have suffered from a stroke or transient ischemic attack, and compared characteristics and outcomes in stroke mimics versus those with ischemic stroke. Overall, 3.5% of tPA treatments were given to stroke mimics. Among them, 38.2% had a final nonstroke diagnoses of migraine, functional disorder, seizure, and electrolyte or metabolic imbalance. Compared with tPA-treated true ischemic strokes, tPA-treated mimics were younger (median 54 versus 71 years), had a less severe National Institute of Health Stroke Scale (median 6 versus 8), and a lower prevalence of cardiovascular risk factors, except for a higher prevalence of prior stroke/transient ischemic attack (31.3% versus 26.1%, all P <0.001). The rate of symptomatic intracranial hemorrhage was lower in stroke mimics (0.4%) as compared with 3.5% in ischemic strokes (adjusted odds ratio, 0.29; 95% CI, 0.17–0.50). In-hospital mortality rate was significantly lower in stroke mimics (0.8% versus 6.2%, adjusted odds ratio, 0.31; 95% CI, 0.20–0.49). Patients with stroke mimics were more likely to be discharged to home (83.8% versus 49.3%, adjusted odds ratio, 2.97; 95% CI, 2.59–3.42) and to ambulate independently at discharge (78.6% versus 50.6%, adjusted odds ratio, 1.86; 95% CI, 1.61–2.14). Conclusions: In this large cohort of patients treated with tPA, relatively few patients who received tPA for presumed stroke were ultimately not diagnosed with a stroke or transient ischemic attack. The complication rates associated with tPA in stroke mimics were low. Despite the potential risk of administering tPA to stroke mimics, opportunity remains for continued improvement in the rapid and accurate diagnosis and treatment of ischemic stroke. Abstract : Supplemental Digital Content is available in the text.